1999
DOI: 10.1007/s004200050414
|View full text |Cite
|
Sign up to set email alerts
|

Manganese exposure in foundry furnacemen and scrap recycling workers

Abstract: Risk assessment based on combined measurements of B-Mn and air-Mn seems to be valid in the interpretation of workers' hazard. Our study indicates that B-Mn may be a valuable parameter for estimating recent exposure (within 1-2 weeks). However, more knowledge is needed about the B-Mn level and its relation to neurological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Researchers have pointed out that the consequences of exposure to manganese in the workplace and uptake of this element in the body will bring about the central nervous system disorder, which would be called manganism, as the complications; there are many similarities with Parkinson's disease [5][6][7][8][9][10][11][12]. One of the most important scientific methods, particularly to determine the exposure to pollutants, is biological monitoring of workplaces [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have pointed out that the consequences of exposure to manganese in the workplace and uptake of this element in the body will bring about the central nervous system disorder, which would be called manganism, as the complications; there are many similarities with Parkinson's disease [5][6][7][8][9][10][11][12]. One of the most important scientific methods, particularly to determine the exposure to pollutants, is biological monitoring of workplaces [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…29 Manganese levels in urine and feces my be used as a marker for exposure to manganese within the previous few hours, whereas manganese can be detected in blood for days to weeks after exposure ceases. 30 Although present occupational standards for exposure levels for manganese in total dust causing neurologic effects have been estimated to be approximately 0.2 mg/m 3 , this threshold limit value (TLV) has never been validated by well-designed scientific studies. 31 Manganeseinduced neurotoxicity has been reported to occur only after chronic exposure to high levels of manganese, 26 usually above the permissible exposure limit ceiling at 5 mg/m 3 set by the Occupational Safety and Health Administration.…”
mentioning
confidence: 99%
“…Under physiological conditions, Mn(II) has been shown to exhibit catalase-like activity (13,14) and is capable of protecting endothelial cells from H 2 O 2 toxicity and from reactive oxygen species (ROS) generated during oxidative burst of neutrophils (15,16). We have shown that in the 0.5-2 mM range Mn(II) induced mitochondria-independent apoptosis in HeLa cells, and it also caused an elevation of ROS and Mn(II)-superoxide dismutase (17).…”
mentioning
confidence: 99%